Assessment of egg quality, food safety, and hygiene practices among commercial and non-commercial farms of Barwala district of Panchkula, Haryana - Rachana Srivastava; Pritam Halder; Poonam Khanna; Savitesh Kushwaha (Journal of Family Medicine and Primary Care)
Background: The aim of the present study was to assess the egg quality, food safety, and hygiene practices in egg production among commercial and non-commercial farms. Methods: A total of six, each commercial and non-commercial farm, were randomly selected form Barwala district, Panchkula, Haryana, for this study in 2019. A detailed interview on hygiene practices of farm workers was conducted. Egg samples were procured for external (N = 60) and internal (N = 24) egg quality determination. The swap samples (N = 24) were also analysed for bacterial contamination. Descriptive statistics were used for reporting the results, and Chi-square test was conducted for determining significant differences between commercial and non-commercial farms. Results: The egg yolk percentage (34.49%) and egg shell percentage (12.76) were higher among non-commercial farms. However, no significant external (P = 0.890) or internal (P = 0.367) egg quality difference was found between commercial and non-commercial farms. The biosecurity and disinfection management, daily waste disposal practice, fly and rodent control practice, farm activity record, and flock health monitoring were relatively better among commercial farms. There were no significant differences found in any of these assessments. The colony forming units (cfu) for salmonella and coliform were acceptable in three and four procured samples from commercial farms, respectively, whereas none were within acceptable levels among non-commercial farms. Conclusion: The internal egg quality, food safety, and hygiene practices were relatively better among commercial farms as compared to non-commercial farms. This requires further validation through a large sample-sized study.